Preparation device of photovoltaic cell string - JIANG ZHIHANG (2023)
The utility model relates to the technical field of photovoltaic module automatic production, and provides a photovoltaic cell string preparation device which comprises a feeding device, a conveying device, a carrying device, a tape manufacturing device, an adhesive tape laying device, a first working platform and a second working platform. The carrying device is used for carrying the battery piece to the first working platform; the strip manufacturing device is used for manufacturing a welding strip set and carrying the welding strip set to the first working platform. The first working platform comprises a first placing platform, a battery piece fixing mechanism and a turnover mechanism; a battery string is placed on each first placing platform; the second working platform comprises second placement platforms and a lifting mechanism, one battery string is placed on each second placement platform, one second placement platform corresponds to one first placement platform, and the battery strings can be placed